The Financial Trap of Short-Term Focus Eroding Long-Term Value in Financial Management: A Theoretical Analysis - Stacey L. Morin (Financial Markets, Institutions and Risks)
Shareholder short-term thinking, driven by a focus on immediate financial returns, poses significant risks to sustainable corporate growth and long-term societal well-being. This paper investigates the mechanisms through which short-term profit maximization fosters corporate decision-making that sacrifices long-term value creation, culminating in organizational greed and systemic inefficiencies. Through a comprehensive literature review and analysis, the paper explored the historical roots of short-termism, regulatory frameworks, and potential solutions to mitigate the adverse impacts of this phenomenon. The relevance of this research lies in the critical role shareholder decision-making plays in shaping corporate strategies, societal outcomes, and the sustainability of the global economy. By addressing how short-term shareholder thinking fosters greed and undermines long-term value creation, this paper highlights the systemic risks and ethical implications of prioritizing immediate financial gains over sustainable growth. This article employs a conceptual analysis grounded in agency theory, stakeholder theory, and the myopic market hypothesis to examine how aligning executive incentives, fostering stakeholder engagement, and countering market pressures can address the negative effects of short-termism. The author leveraged the concepts from these theories. The author's contribution to solving the scientific problem under study involves a conceptual framework application for mitigating short-term shareholder focus and concentrating on long-term value. The findings underscore the need for governance reforms and stakeholder-centric approaches, making the research pivotal for fostering resilient and responsible corporate practices that benefit both businesses and society at large.